THE ROLE OF THE MANUSCRIPT COLLECTOR IN BANDA ACEH - Evi Mandasari; Harmansyah; Istiqomatunnisak (The Department of Islamic History and Culture in cooperation with the Center for Islamic History and Culture in Aceh and Malay World Studies (PUSAKA), Universitas Islam Negeri Ar-Raniry Banda Aceh, Aceh, Indonesia, 2022)
The goal of this research is to determine what function manuscript collectors play in Banda Aceh and what manuscript collections are available to them. This study used a qualitative research method in which the data was collected by observation, interviews, and documentation procedures, as well as a literature review and previous references. According to the findings of the study, manuscript collectors in Banda Aceh play a variety of activities, including caring for and preserving manuscripts, teaching, using social media, and motivating the younger generation. Tarmizi Abdul Hamid and Masykur Syafruddin are two manuscript collectors discussed by the authors. The collections of these two individuals are very distinct. The collections of these two collectors are quite distinct. Masykur has roughly 495 manuscript collections that have been inventoried with varied themes, whereas Tarmizi has 598 collections. The lack of funding and human resources for manuscript maintenance are problems that collectors encounter in general.